Single Parenting and Childhood Visual Impairment: Coping, Caregiving Burden, and Implications for Family Support Systems An Interpretative Phenomenological Analysis - Anggria Vesty Wulandari; Alfito Rizki Saputra; Krisna Maulana; Kholifah Umi Sholihah (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
Single parents raising children with visual impairments face persistent caregiving demands involving emotional strain, economic vulnerability, and limited institutional support. Although parenting stress in disability contexts has been widely documented, limited attention has been given to how coping strategies are shaped by systemic caregiving conditions, particularly in single-parent households. This study employed an Interpretative Phenomenological Analysis (IPA) approach to explore the lived experiences and coping strategies of single parents raising children with visual impairments in a resource-constrained context. Three single parents aged over 40 years were recruited through purposive sampling. Data were collected through semi-structured interviews and non-participant observations and analyzed thematically following IPA procedures. The findings indicate that caregiving stress is strongly influenced by structural factors, including financial pressure, limited access to specialized educational services, and the absence of a caregiving partner. Participants adopted problem-focused coping strategies such as restructuring the home environment, systematic daily caregiving planning, and consulting special education teachers when support was partially available. Emotion-focused coping strategies, including acceptance and positive reframing, were used to manage long-term stressors beyond individual control. Overall, coping among single parents emerged as contingent upon the interaction between individual capacities and systemic support availability. These findings highlight the need for integrating caregiver-focused support within special education services and strengthening community-based support networks to improve family well-being and educational outcomes for children with visual impairments.